Implementation of Smart ASN Principles in Metro City - Bunga Putri Ananda; Yulianto Yulianto; Ita Prihantika (Utan Kayu Publishing, 2025)
Civil Servants (ASN) are part of government organizations, required to be adaptive in changes such as digitalization in the current era of the Industrial Revolution 4.0. The linkage between ASN and digitalization, the Ministry of Administrative and Bureaucratic Reform has created a new breakthrough called Smart ASN. This study aims to determine the extent to which the principles of Smart ASN are applied in Metro City. The research uses a quantitative approach with a descriptive method. The data used are primary data obtained through questionnaires. The respondents are civil servants working in the Regional Government Organizations of Metro City, aged 40 years or younger, totaling 218 individuals. The study employs Vroom's expectancy theory. The indicators used for Smart ASN are the eight principles of Smart ASN, including integrity, professionalism, nationalism, global insight, mastery of IT and foreign languages, hospitality, networking, and entrepreneurship. The results show that the implementation of Smart ASN principles has been very successful, with a percentage of 91%, indicating the successful implementation of Smart ASN principles by civil servants in Metro City.